Ultrasonography of udder parenchymal tissue of Murrah and Swamp buffalo calves - Mokhamad Fakhrul Ulum; Hammada Raudlowi; Rantan Krisnan (Indonesian Center for Animal Research and Development (ICARD), 2017)
The examination of udder through a parameter such as parenchymal tissue (PAR) and mammary fat pads (MFP) can be used to evaluate health status and the development of mammary gland. This research was conducted to evaluate the PAR and MFP of Murrah (n=4) and Swamp (n=4) buffalo heifer calve udder using brightness-mode ultrasonography transcutaneously. Eight buffalo consisted of Murrah (n=4) and Swamp (n=4) buffalo aged of six months old reared at Indonesian Research Institute for Animal Production, Ciawi, Bogor were used this study. Ultrasonography imaging was performed on the udder nipple for the four quarters: left front, left back, right front, and right back. The ultrasonography image was evaluated and then assessed for score, echogenicity and PAR area on MFP. The results showed that sonogram PAR was aniconic to hypoechoic, while the MFP was hypoechoic to hyperechoic. Even though there was a variation in the four quarters of udder, Murrah buffalo calve had the highest (P>0.05) value of score, echogenicity, and PAR area compared to the Swamp buffalo.